Resistance to antimicrobial agents of Vibrio cholerae El Tor strains isolated during the fourth cholera epidemic in the United Republic of Tanzania - Towner, K. J. (1980)
Isolates of Vibrio cholerae obtained immediately after the outbreak of the fourth recorded epidemic of cholera in the United Republic of Tanzania were sensitive to tetracycline, but after five months of its extensive therapeutic and prophylactic use, 76% of the isolates were observed to be resistant to this and other antimicrobial agents. The appearance of resistance was found to be due to the rapid spread of antibiotic resistance plasmids belonging to the C incompatibility complex. Although most plasmid incompatibility groups have been shown to be unstable in V. cholerae, the strains found in the present epidemic seem to carry a plasmid belonging to one of the few relatively stable groups. These findings emphasize the importance of monitoring any emergence of bacterial resistance that may occur when mass prophylaxis programmes are in operation and also the importance of determining the genetic basis of the resistance mechanism.